2013
DOI: 10.1155/2013/673798
|View full text |Cite
|
Sign up to set email alerts
|

How Reliable Are Hematological Parameters in Predicting UncomplicatedPlasmodium falciparumMalaria in an Endemic Region?

Abstract: Background Malaria remains endemic in Sub-Saharan Africa. Hematological changes that occur have been suggested as potential predictors of malaria. This study was aimed at evaluating the diagnostic relevance of hematological parameters in predicting malaria. Methods A cross-sectional study involving 370 patients with signs and symptoms of malaria was conducted at Mulago Hospital, Kampala, from May, 2012 to February, 2013. Thin and thick blood films were prepared for each patient and stained with Giemsa to aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 32 publications
12
43
0
1
Order By: Relevance
“…7 This study showed an increase in monocyte count in malaria patients with a mean of 9.4 (5.4)%. This result was similar to Muwonge et al 9 who showed that an average count of monocytes in patients with malaria amounted to 10.89 (6.23)%. Monocytosis was one of hematological changes consistent in malaria.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…7 This study showed an increase in monocyte count in malaria patients with a mean of 9.4 (5.4)%. This result was similar to Muwonge et al 9 who showed that an average count of monocytes in patients with malaria amounted to 10.89 (6.23)%. Monocytosis was one of hematological changes consistent in malaria.…”
Section: Resultssupporting
confidence: 91%
“…Hematological changes were found in patients with malaria such as normocytic normochrome anemia and thrombocytopenia. 12 Muwonge et al 9 in Uganda reported an increased levels of monocytes to 61 malaria patients of about 10.89 (6.23). However, studies of Chandra & Chandra 13 in India during August 2008 until August 2010 reported that thrombocytopenia (platelet count <150,000/ mm 3 ) was significant in acute malaria compared to controls with a sensitivity of 87.2% and a specificity of 65%.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar results were reported in patients with uncomplicated malaria where the authors indicated that, uncomplicated malaria was associated with milder biochemical alteration and haemolysis as opposed to complicated/severe malaria [26]. A study done at ECWA Community Health Centre, Bukuru, Jos in Nigeria however showed significant reduction of the haematocrit of malaria samples compared to healthy controls [22].…”
Section: Discussionsupporting
confidence: 70%
“…Entry of P. falciparuminto erythrocytes usually leads to a marked increase in secretion of inflammatory cytokines (TNFα, IL-1, IL-10, and IFN γ ), endothelial cell activation (due to overexpression of cell adhesion molecules; ICAM-1, VCAM-1), activation of the coagulation cascade (due to platelet consumption and endothelial damage), and sequestration of parasitized RBCs (Haruna et al, 2013). Certain haematological changes which include low platelet count, haemoglobin concentration and hematocrit have been reported to be associated with malaria (Kumar and Shashirekha, 2006).…”
Section: Introductionmentioning
confidence: 99%